DETERMINANT OF BUSINESS GROWTH IN SMALL MILLING - Muhammad Reza Putra; Zulki Zulkifli Noor (Dinasti International Journal of Management Science, 2020)
The purpose of this research are the magnitude of managerial factors, namely the spirit of entrepreneurship, competence, the role of leadership and business partnerships in the small rice mill industry in the DKI Jakarta rice center. This research is an research, because in accordance with the purpose of this study to explain the relationship between the concepts of research and hypothesis testing in order to make decisions inductively or generalize. Considering its purpose, this study wants to obtain a description or description of managerial factors namely entrepreneurial spirit, competence, leadership role and business partnership and examine its effect on fund management whose impact on financial performance and its implications for business development. The finding of this research is the entrepreneurial spirit which consists of an innovative dimension, a proactive dimension and a risk taking dimension are on a sufficient scale. It can be said that small scale rice mill entrepreneurs in DKI Jakarta rice centers are quite innovative, quite proactive and take moderate business risks.